Fiction as a lie and the fruit of imagination represented by English and Russian idioms (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with semantics, inner form and pragmatic impact of Russian and English idioms with the general meaning of fiction. The author reveals the common factors affecting the attitudes of Russian and English native speakers to phenomenon towards fiction in everyday communication.
Keywords: idiom; fiction; pragmatic impact; fluctuation; correlation; categorization; discourse functioning